Mesozooplankton grazing in the coastal Gulf of Alaska: Neocalanus spp. vs. other mesozooplankton - Liu, Hongbin; Dagg, Michael J.; Napp, Jeffrey M.; Sato, Riki (ICES Journal of Marine Science, 2007)
<qd> Liu, H., Dagg, J. M., Napp, J., and Sato, R. 2008. Mesozooplankton grazing in the coastal Gulf of Alaska: Neocalanus spp. vs. other mesozooplankton. – ICES Journal of Marine Science, 65. </qd>Three species of large calanoid copepod, Neocalanus flemingeri , Neocalanus plumchrus , and Neocalanus cristatus , dominate the spring biomass of mesozooplankton in the Subarctic Pacific. We compared the grazing impact of Neocalanus species on phytoplankton with grazing by the remainder of the mesozooplankton community in the coastal and shelf waters of the Gulf of Alaska during spring and summer 2003. Neocalanus spp. and other mesozooplankton fed mainly on particles >20 µm, and phytoplankton in the smaller size-fractions (<20 µm) increased in the presence of mesozooplankton, possibly because of a trophic cascade resulting from mesozooplankton consumption of microzooplankton. Neocalanus spp. accounted for most of the mesozooplankton biomass and herbivory in the shelf water of the Gulf of Alaska and in the Prince William Sound (PWS) during April/May. The biomass of other mesozooplankton (mostly small copepods) varied seasonally and spatially; it did not increase in summer after the descent of Neocalanus spp. from the surface layer. On the basis of the clearance rates obtained from our experiments, in spring, grazing by Neocalanus spp. and the remaining mesozooplankton consumed ∼10% of daily growth of phytoplankton >20 µm in the outer-shelf region, where chlorophyll a concentrations were <0.5 mg m−3, and in PWS. Mesozooplankton consumed a smaller percentage of the >20 µm daily phytoplankton production in the inner- and mid-shelf regions where chlorophyll a concentrations were typically >5 mg m−3 with blooms of large diatoms. In summer, without Neocalanus spp. in the surface layer, mesozooplankton grazing accounted for a very small proportion of phytoplankton production across the whole shelf.